Assessment of Thermal and Mechanical Properties of Cement-Based Materials—Part 1: Crumb Rubber Concrete - Alexandra Cojocaru; Dorina Nicolina Isopescu; Sebastian George Maxineasa; Sergiu George Petre (Buildings, 2023)
The energy performance of buildings and the high consumption of traditional building materials are considered to be the most important aspects that are related to the implementation of the sustainability concept in the construction industry with respect to the natural environment. At the same time, another important global ecological problem is represented by different types of waste resulting from existing industries. Therefore, it is necessary that civil engineering specialists find new solutions and materials that can improve the thermal and environmental performances of buildings by taking into consideration the large amounts of existing waste. Taking into account the fact that concrete is the most used material in the construction sector and that concrete elements have a significant influence over the overall energy performance of a building, the present paper takes under observation the use of tire rubber waste as a replacement for concrete aggregates. This study considers a replacement of 10%, 20%, and 30% of the 4–8 mm aggregates with crumb rubber cylindrical granules. The resulting values show an improvement in the thermal performance, but at the same time, the mechanical properties are reduced.